2012
DOI: 10.5120/8134-1823
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Decision Making System for Breast Cancer Data

Abstract: Data Mining is a technique to extract the hidden knowledge of information. Among several data mining methods classification is especially useful in the field of medical diagnosis for decision making. In this study, a hybrid approach: CART decision tree classifier with feature selection and boosting ensemble method has been considered to evaluate the performance of classifier. Various Breast cancer data sets are considered for this study as breast cancer is one of the leading causes of death in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Moreover, tree‐based methods have proved useful for building recommender systems in different areas outperforming other approaches (Utku et al, 2015). However, the accuracy of prediction may suffer from both the size of the available data set (Bar et al, 2013; Ghimire et al, 2012) and the number of features (Lavanya & Rani, 2012). Our previous studies have demonstrated the superior performance of tree‐based ensembles relative to single decision‐trees, as well as their dependency on the number of available features (Almomani et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, tree‐based methods have proved useful for building recommender systems in different areas outperforming other approaches (Utku et al, 2015). However, the accuracy of prediction may suffer from both the size of the available data set (Bar et al, 2013; Ghimire et al, 2012) and the number of features (Lavanya & Rani, 2012). Our previous studies have demonstrated the superior performance of tree‐based ensembles relative to single decision‐trees, as well as their dependency on the number of available features (Almomani et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The performance of ensemble models in medical diagnosis has not been extensively studied, with the exception of [27] and [15], which show that bagging and boosting learning perform better than a single model. The fact that the medical dataset is typically class-imbalanced is yet another factor that can make things more complicated.…”
Section: Related Workmentioning
confidence: 99%
“…The results for the best implementation of a SVM put the classification accuracy at about 96.9957%. In Lavanya and Rani [38], the classification and regression trees (CART) method was tested on the Breast Cancer (Original) data set. This method uses recursive partitioning in a regression tree algorithm hybridized with bagging, a bootstrap aggregation method.…”
Section: Observations On Breast Cancermentioning
confidence: 99%